A polarization image enhancement method for glioma - Liu, Yi-Rong; Liang, Chao-Feng; Zhao, Han-Qiao; Ou, Yun-Mou; Wu, Jian (Frontiers in Neuroscience, 2023)
Polarization imaging technique (PIT) based on backward scattering 3×3 Mueller matrix polarization imaging experimental setup is able to study the optical information and microstructure of glioma and non-glioblastoma tissues from clinical treatment. However, the image contrast of Mueller Matrix Elements (MME) is far from sufficient to provide supplemental information in the clinic, especially in off-diagonal MME. The aim of this work is to propose an innovative method to improve the contrast and quality of PIT images of glioma and non-glioma tissues. The work first confirms the robustness of the method by evaluating the enhanced images and assessment coefficients on ex-vivo unstained glioma and non-glioma sample bulks, then the optimally enhancement results are tested and presented based on the multi-sample tests. The proposed method can further be used to identify glioma and residues in the intraoperative environment with PIT.